Air Weapons and Licensing (Scotland) Act 2015 : consultation on : guidance on the provisions for licensing of sexual entertainment venues and changes to licensing of theatres : summary of responses.: consultation on : guidance on the provisions for licensing of sexual entertainment venues and changes to licensing of theatres : summary of responses. (2018) - Scotland., Criminal Law, Practice; Licensing Unit,
No abstract available